Tuft cells utilize taste signaling molecules to respond to the pathobiont microbe Ruminococcus gnavus in the proximal colon - Lei, Hao; Yu, Defu; Xue, Yan-Bo; Li, Yi-Hong; Gong, Shi-Meng; Peng, Yuan-Yuan; Liu, Kai-Fang; Buratto, Damiano; Yang, Yisen; Zhang, Sai-Sai; Wu, Min; Zhou, Ruhong; et al. (Frontiers in Immunology, 2023)
Tuft cells are a type of rare epithelial cells that have been recently found to utilize taste signal transduction pathways to detect and respond to various noxious stimuli and pathogens, including allergens, bacteria, protists and parasitic helminths. It is, however, not fully understood how many different types of pathogens they can sense or what exact molecular mechanisms they employ to initiate targeted responses. In this study, we found that an anaerobic pathobiont microbe, Ruminococcus gnavus (R. gnavus), can induce tuft cell proliferation in the proximal colon whereas the microbe's lysate can stimulate these proximal colonic tuft cells to release interleukin-25 (IL-25).Nullification of the Gng13 and Trpm5 genes that encode the G protein subunit G13 and transient receptor potential ion channel Trpm5, respectively, or application of the Tas2r inhibitor allyl isothiocyanate (AITC), G protein Gβ subunit inhibitor Gallein or the phospholipase Cβ2 (PLCβ2) inhibitor U73122 reduces R. gnavus-elicited tuft cell proliferation or IL-25 release or both. Furthermore, Gng13 conditional knockout or Trpm5 knockout diminishes the expression of gasdermins C2, C3 and C4, and concomitantly increases the activated forms of caspases 3, 8 and 9 as well as the number of TUNEL-positive apoptotic cells in the proximal colon. Together, our data suggest that taste signal transduction pathways are not only involved in the detection of R. gnavus infection, but also contribute to helping maintain gasdermin expression and prevent apoptotic cell death in the proximal colon, and these findings provide another strategy to combat R. gnavus infection and sheds light on new roles of taste signaling proteins along with gasdermins in protecting the integrity of the proximal colonic epithelium.